If it's not what You are looking for type in the equation solver your own equation and let us solve it.
1/6x-3=5/6
We move all terms to the left:
1/6x-3-(5/6)=0
Domain of the equation: 6x!=0We add all the numbers together, and all the variables
x!=0/6
x!=0
x∈R
1/6x-3-(+5/6)=0
We get rid of parentheses
1/6x-3-5/6=0
We calculate fractions
-3!=0
There is no solution for this equation
| 7=k9 | | 0.9x-0.3=4 | | 6(x+10)=42 | | 3x+8=4(x-2) | | 4x-1=-+9 | | 3x2=375 | | 4(x-3)=5(2x+7 | | 2(x+0.6)5(1.02-x)=0 | | 1.3x=36 | | 3x-10=4x=13 | | 7y-12-4y+7=0 | | j2+ 9= 11 | | 8x+2=x+2 | | 2/714q+7/2-3q=9 | | -12+x=35 | | 16x2=-96 | | 15v-29=-13 | | 9(3x−16)+15=6x−24 | | 5(n+6)=60 | | 4+x/3=10 | | 16x2=0 | | 2(x+5)=2x=5 | | -6.4-6.5x=-103.12 | | 18x+34-6/x=12 | | 2x-8=7x=5 | | 9x=280-10 | | 0.25(x+2)=8 | | 16x2=109 | | 3n+16=18 | | (x+2)(x+3)=24 | | 104+2x+2=180 | | 3x-9=6x-8 |